Getting Promoted: Turning your Clinical Work into Scholarship - Emily Walvoord; Wendy Hobson-Rohrer; Stephen Bogdewic (Association of American Medical Colleges, 2014)
Abstract Introduction The demonstration of scholarship is an essential part of every promotion dossier. Clinical faculty need to know how to use their clinical, educational, and service efforts to fulfill scholarship requirements. This workshop employs a number of interactive strategies to help faculty develop plans for crafting their current activities and ideas into scholarly products. It is aimed at fellows and junior/midlevel faculty interested in getting promoted, as well as senior-level faculty interested in mentoring junior faculty. Methods In it, participants assess their current career and set scholarship goals for the future. The resource briefly reviews the definition of scholarship and gives concrete examples of how busy clinicians develop scholarship. This is followed by a review of the quality improvement cycle of Plan-Do-Study-Act and how it can be used for scholarship development and documentation. The tenets of the dissemination of scholarship (i.e., public, peer reviewed, and a platform for others) are discussed. Participants then work in small groups to devise a dissemination plan for example scholarly activities. Participants also use a detailed worksheet tool to review their current activities and formulate plans for their own scholarship development and dissemination. Small groups then give each other feedback about a personal scholarship plan. The moderators discuss pitfalls that junior faculty often fall into that derail scholarship productivity. The session concludes with questions and sharing of opportunities and challenges as a large group. A toolkit with references and resources is provided. Results Feedback from the participants at the Pediatric Academic Societies meetings gave this module an overall rating of 3.78 (on a scale of 1 to 4). Comments included "One of the best workshops I've attended," "Handouts were focused and useful," and "Excellent use of limited slides, succinct, and to the point." Discussion This workshop was developed to fill a need in faculty development related to scholarly activities and has effectively met this purpose.